Games and Play in the Creative, Smart and Ecological City (Taylor & Francis, 2021)
Regional and local governments have long recognised the potential for films, television shows, novels and other media texts that are set in their city or country to attract tourists. Although there is a wealth of scholarship on how real-world locales are represented in digital games, to date scholars have largely overlooked the potential for videogames to likewise attract fans and 'pilgrims' to the locations in which they are set. This chapter addresses this gap through the case study of Yokosuka City in Japan, which has recognised the cult classic videogame Shenmue (Sega AM2, 1999) as a drawcard for tourists and fans outside the city. Through its 'Sacred Spot Guide Map', Yokosuka City officials provide a guide for tourists seeking to visit locations depicted in the game that contrasts their fictional and real-world counterparts and invites visitors to explore its spaces through affiliated promotion campaigns. Drawing on an analysis of the Guide Map, an interview with its creators and field observation in Yokosuka itself, we examine the potential for the Guide Map and other forms of city-funded videogame tourism to put cities overwise overlooked in travel guides and reviews 'on the map' and boost their local economy.
English
Keywords: Applied ecology; City and town planning: architectural aspects; Urban communities; ecological city; games; tourism